Effects of Capital Structure on Firms Financial Performance Case Study Commercial Banks in Mogadishu Somalia - Abdi, Bile Mohumed; Ali, Abdullah Ibrahim (IJRDO - Journal of Business Management, 2016)
The purpose of this study was is to investigate the influence of capital structure on firms financial performance a case study of commercial banks in Mogadishu Somalia. Results indicates that equity finance, debt finance, optimal capital structure had significant effect on firms financial performance in commercial banks in Mogadishu Somalia. The study findings indicated that there was a strong positive relationship (R= 0.637) between the variables. From the study findings it was conclude that equity finance, debt finance, optimal capital structure had a strong positive relationship on firms financial performance in a commercial banks in Mogadishu Somalia because there was evident that at 100% confidence level.